2020
DOI: 10.3390/agronomy10101536
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change May Imperil Tea Production in the Four Major Tea Producers According to Climate Prediction Models

Abstract: The threat of accelerating climate change on species distribution now and in the future is a topic of increasing research interest. However, little work has been undertaken to assess how shifting climates will affect the suitability of tea cultivation. Therefore, we used MaxEnt modelling to project the impact of current and future climatic scenarios on the potential distribution of tea across the four tea-producing countries of China, India, Kenya and Sri Lanka. Projections were made for the years 2050 and 207… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…51,85 By focusing on climate extremes, we have shown that under the high-emission scenario, some of these areas (particularly Central America and Brazil) could experience considerably more and longer dry and hot periods, which coffee plants are particularly susceptible to. We identify similar high risks for tea producers as in other studies, 86,87 which also suggest a contraction of tea production areas particularly in Central and East Africa.…”
Section: Discussionsupporting
confidence: 86%
“…51,85 By focusing on climate extremes, we have shown that under the high-emission scenario, some of these areas (particularly Central America and Brazil) could experience considerably more and longer dry and hot periods, which coffee plants are particularly susceptible to. We identify similar high risks for tea producers as in other studies, 86,87 which also suggest a contraction of tea production areas particularly in Central and East Africa.…”
Section: Discussionsupporting
confidence: 86%
“…Prolonged drought, waterlogged conditions, and low temperature (less than 12°C and above 30°C) are not suitable for the growth of tea. The minimum annual rainfall of 1200 mm and 70-75% average relative humidity is suitable for the growth of tea plant (2).…”
Section: Suitable Environment Conditionmentioning
confidence: 99%
“…It is vital to identify the optimal climate and soil to guarantee the suitable growth and harvesting of tea. Previous studies have employed various methodologies, including the Delphi method and GIS [100] , Sentinel-2 image data [81] , and integrating Sentinel-2 images with GIS [101] to evaluate tea plantation suitability. Factors considered for tea cultivation suitability include climate [102] , soil [103] , terrain, human-related factors, ecological economy factors, and tea plant growth information [104] .…”
Section: Tea Cultivation Suitability Assessment By Remote Sensing And...mentioning
confidence: 99%